Fiscal Rules in a Volatile World : A Welfare-Based Approach - Restrepo, Jorge (IMF Working Papers; Working Paper ;, 2011)
It is widely agreed that a fiscal rule should boost discipline and credibility, reduce macroeconomic volatility, and be easily understood. To support such goals, a government may run structural surpluses and accumulate a precautionary cushion of assets on behalf of agents who do not enjoy access to capital markets. As an additional criterion, that level of assets should be bounded. We provide an example of a structural surplus rule that satisfies all such criteria. In our general equilibrium simulations, we show that such a rule benefits credit-constrained consumers but may hurt others.